Psalms en hulle Sitz(e) im Leben. 'n Analise aan die hand van Psalm 55 en 74 - Human, Dirk J. (Verbum et ecclesia, 1998)
It is hermeneutically unthinkable to expose any Old Testament text, without taking its historic and/or cultic Sitz im Leben into consideration. This especially applies for the texts of the psalms. But, vague formulations and generalised language, though, make this effort in the psalms extremely difficult. In view of the eclectic chosen examples of Psalms 55 and 74, this article shows how several Sitz(e) im Leben are identified by exegetes for the understanding of a psalm. More than one historical situation could have instigated the origin and content of a psalm. To determine the socalled "original" Sitz of psalms, is therefore almost impossible. But, this state of affairs should not cause the exegete or preacher to be sinical about exegetical method or diachronic research of psalm texts. Various identified Sitz(e) behind the text should create a common dealer - an athmosphere or interpretation-direction - which create afreedom in the exegete or reader's mind to identifY suitable situations for the reinterpretation or actualisation of a psalm. In this regard, a literary or textimmanent reading is not complete without diachronic exegesis. Despite uncertainty about the so-called "original" Sitz im Leben behind most psalms, exegetes should be more than enthusiastic to struggle with the search for a historic or cultic Sitz(e) behind the text. This will add value to the understanding of every psalm.